2004
DOI: 10.1037/1064-1297.12.3.180
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing and Subjective Effects of Methylphenidate: Dose and Time in Bed.

Abstract: So that reinforcing and subjective effects of methylphenidate as a function of dose and level of sleepiness could be evaluated, 21 volunteers received methylphenidate (5, 10, or 20 mg) or placebo on 2 sampling days. After 4 and 8 hr time in bed (TIB), they chose their preferred capsule on 5 days. Methylphenidate was chosen more frequently after 4 hr TIB (60%) than it was after 8 hr TIB (33%). The strongest preference (68%) was seen in the 10-mg group. At 10 and 20 mg, stimulant-like subjective effects were rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…However, the similarity of the findings between the two studies – a laboratory-controlled self-administration study and a treatment study – as well as prior studies showing a potential role of sleepiness in the reinforcing and subjective effects of stimulants (Roehrs et al, 2004) and previously demonstrated effects of poor sleep on factors such as cognition, mood, and impulsivity, support the likelihood that there is a causal relationship between sleep and cocaine use in chronic cocaine users. This interpretation of the data is also supported by similar findings relating sleep to alcohol use (Allen et al, 1975, 1977; Benca et al, 1992; Brower and Hall, 2001; Brower, 2003; Colrain et al, 2009), and by longitudinal studies that suggest a “bi-directionality” in the relationship between sleep and substance use (Pasch et al, 2012; Shibley et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…However, the similarity of the findings between the two studies – a laboratory-controlled self-administration study and a treatment study – as well as prior studies showing a potential role of sleepiness in the reinforcing and subjective effects of stimulants (Roehrs et al, 2004) and previously demonstrated effects of poor sleep on factors such as cognition, mood, and impulsivity, support the likelihood that there is a causal relationship between sleep and cocaine use in chronic cocaine users. This interpretation of the data is also supported by similar findings relating sleep to alcohol use (Allen et al, 1975, 1977; Benca et al, 1992; Brower and Hall, 2001; Brower, 2003; Colrain et al, 2009), and by longitudinal studies that suggest a “bi-directionality” in the relationship between sleep and substance use (Pasch et al, 2012; Shibley et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…While novel, these results are not completely surprising given the clinical literature (Brower, 2001; Clark et al, 1998; Foster and Peters, 1999; Gillin et al, 1994; Roehrs et al, 1999, 2004) and the known neurochemical consequences of sleep deprivation. For instance, sleep deprivation has been shown to augment dopamine (DA) activity in the mesocorticolimbic reward system (Asakura et al, 1992; Brock et al, 1995; Farooqui et al, 1996; Hernández-Peón et al, 1969).…”
Section: Discussionmentioning
confidence: 75%
“…Clinical studies suggest that sleep deprivation is one such factor, and both subjective (self-administered questionnaire scores) and objective (polysomnographic sleep parameters) measures of poor sleep quality have been shown to predict relapse in humans (Brower, 2001; Clark et al, 1998; Foster and Peters, 1999; Gillin et al, 1994). Also, acute sleep deprivation has been shown to increase preference for methylphenidate (Roehrs et al, 1999, 2004). In addition, we have previously demonstrated in rats that acute sleep deprivation increases the rate and efficiency (i.e., the goal-directed nature of responding) of cocaine self-administration during PR testing, even in rats that maintain low levels of drug intake (i.e., low drug-takers; Puhl et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also possible that poor sleep contributes to drug use (e.g. Mednick et al, 2010; Roehrs et al, 2004); the association of longer periods of use with greater sleep deficits does not rule out this possibility, as longer periods of use may themselves reflect factors that contribute to an increased baseline risk for cocaine dependence. In addition to years of cocaine use, recent quantity of alcohol use affected sleep.…”
Section: 0 Discussionmentioning
confidence: 99%